Argeneau : Immortal Angel - Book 31 - Sands, Lynsay (New York, NY : Avon Books, an imprint of HarperCollinsPublishers, 2020)
"For almost two centuries, Ildaria Garcia has been on the run, a trouble magnet with a knack for taking down bad guys. Lately, her vigilante tendencies have drawn unwelcome attention to her fellow Immortals. Forced to relocate, Ildaria is supposed to lay low in a new town. Instead, she quickly entangles herself with six and a half feet of muscular, tattooed trouble. Joshua James Simpson Guiscard, aka G.G., knows a lot about Immortals--enough to make him wary. Yet from the moment Ildaria walks into his club, he feels desire stronger than anything hes known. Accepting the fact that they might be life mates is disconcerting. But when her past catches up to them, G.G. faces a choice--confront his demons at last, or lose a passion thats hot as hell."--Publishers description.
Keywords: Vampires -- Fiction; Man-woman relationships -- Fiction; Romance fiction; Fantasy fiction; Paranormal fiction